Hidroxiapatitas modificadas com óxidos de Si, Ti e Zr avaliados para aplicações como material odontológico - Costa, Wanderson Barros (2018)
Hydroxyapatite is a biomaterial with good application in bone grafts, however, it has limitations such as its low mechanical resistance. The alternative of altering the mechanical properties of this phosphate is the incorporation of metallic oxides both in the crystalline lattice and in the apatite surface. In this work, hydroxyapatite powders modified with silicon, titanium and zirconium from alkoxides with proportions of 25, 50, 75, 100 and 300% in relation to the hydroxyapatite sites present in hydroxyapatite were synthesized by chemical co-precipitation and addition of the alkoxides in solids was given by sol-gel method. The obtained materials were characterized by X - ray diffractometry, Fourier transform infrared spectroscopy, X - ray fluorescence analysis, diffuse reflectance spectrophotometry in UV - VIS and thermogravimetric analysis before the interaction with glass ionomer cement. The results of the proposed modifications with alkoxides suggested that there was an immobilization of the same on the surface of the solid, however, without significant changes in the hydroxyapatite structure, observed by the half height width of the synthesized powders. The solids modified with the titanium and zirconium ions showed a greater immobilization of the same on the surface of the phosphate. A pre-test for possible dental application of the materials through the evaluation of marginal microleakage with incorporation in the glass ionomer cement indicated that the solids showed better performance than the pure hydroxyapatite. The best results were for the samples of hydroxyapatites modified with zirconium (300%), followed by titanium (300%) and silicon (100%), different from the tests with pure apatite, in which the results were of a greater infiltration and not fixation of dental cement.